Question: Converting a parametric representation of a function

Very likely there is a very simple solution to this question, but I searched Maple's help pages and this forum and didn't find a solution.  Probably because I don't use the correct English terms.

given two functions

(1) X := x->f1(t);

(2) Y := y->f2((t);

witth t = -infinity...infinity; f1 and f2 arbitrary functions of a parameter t

How I can get the function

Y := x->f3(x);

It is a quite trivial problem I agree. On a sheet of paper I would transform (1) into T := t->f4(x) and then substitute this function into f2, but how I can get Maple to do that.


Please Wait...